2014
DOI: 10.1603/me13153
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Taxonomic Status of Some Species Included in the Shannoni Complex, With the Description of a New Species of <I>Psathyromyia</I> (Diptera: Psychodidae: Phlebotominae)

Abstract: The Shannoni complex, comprising sand flies belonging to the subgenus Psathyromyia (Psathyromyia) Barretto, consists of several species, of which the females have banana-shaped spermathecae and the males have digitiform parameres on the terminalia. Among these species, Psathyromyia shannoni (Dyar) and two taxa considered as its junior synonyms (Phlebotomus limai Fonseca and Phlebotomus bigeniculatus Floch & Abonnenc), Psathyromyia pestanai (Barretto & Coutinho), and a new species are the focus of this study. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
2
26
0
2
Order By: Relevance
“…Further, among other specimens identified as Pa. shannoni, including those from Argentina, there exists another species, Pa. baratai, recently described by Sábio et al (2015). Based on the morphological differences presented by Sábio et al (2014) to distinguish Pa. bigeniculata from Pa. shannoni the presence of Pa. bigeniculata in the Chaco region is confirmed, not only at the sites sampled in this study but also by specimens existing in previous collection . These findings reinforce Sábio´s proposal, and emphasize the need for a review of the specimens identified as Pa. shannoni in Argentina, to determine the actual distribution of Pa. bigeniculata and Pa. baratai, and the possible presence of other members of the Shannoni complex.…”
Section: New Recordings In Argentinasupporting
confidence: 76%
See 1 more Smart Citation
“…Further, among other specimens identified as Pa. shannoni, including those from Argentina, there exists another species, Pa. baratai, recently described by Sábio et al (2015). Based on the morphological differences presented by Sábio et al (2014) to distinguish Pa. bigeniculata from Pa. shannoni the presence of Pa. bigeniculata in the Chaco region is confirmed, not only at the sites sampled in this study but also by specimens existing in previous collection . These findings reinforce Sábio´s proposal, and emphasize the need for a review of the specimens identified as Pa. shannoni in Argentina, to determine the actual distribution of Pa. bigeniculata and Pa. baratai, and the possible presence of other members of the Shannoni complex.…”
Section: New Recordings In Argentinasupporting
confidence: 76%
“…However, one of the species considered as its junior synonym, Pa. bigeniculata, has been revalidated and the majority of specimens of the cis-Andean region that had been identified as Pa. shannoni belong in fact to Pa. bigeniculata (Sábio et al 2014). On the basis of the observations of these latter authors, Phlebotomus microcephalus (Barretto & Duret), another junior synonym of Pa. shannoni described from Chaco, Argentina, needs to have its taxonomic status evaluated.…”
Section: New Recordings In Argentinamentioning
confidence: 99%
“…Through this experiment was observed that the grouped females laid more eggs on average (6.1) than the individualized ones (3.9). However, these data were not used because from 30 emerged females (F1), seven belonged to the species Psathyromyia bigeniculata (Sábio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Outra questão a ser investigada no início do presente estudo era um táxon que vinha sendo identificado como Pa. abonnenci no Sudeste e Sul do Brasil (CRUZ et al, 2011), devido a características da genitália masculina bem parecidas às desta espécie, mas com um padrão de coloração torácica distinto. Além disto, Phlebotomus microcephalus, até então, considerado como sinônimo-júnior de Pa. shannoni, pela sua descrição, era morfologicamente mais próximo ao táxon registrado por CRUZ et al (2011) (SÁBIO et al, 2014). Além disso, as fêmeas do complexo Shannoni são morfologicamente muito semelhantes e os machos que contribuem para correta identificação das espécies, nem sempre são comumente coletados.…”
Section: Justificativas Do Estudo Do Subgênero Psathyromyiaunclassified
“…SÁBIO et al (2014) presumiam, sendo constituído dos seguintes táxons: Pa. abonnenci, Pa. baratai, Pa. barretti, Pa. bigeniculata, Pa. dendrophyla, Pa. lerayi, Pa. limai, Pa. ribeirensis, Pa. scaffi, Pa. shannoni e Pa. souzacastroi.…”
Section: Objetivos Específicosunclassified